Center‐out echo‐planar spectroscopic imaging with correction of gradient‐echo phase and time shifts. Issue 1 (27th July 2012) - Labadie, Christian; Hetzer, Stefan; Schulz, Jessica; Mildner, Toralf; Aubert‐Frécon, Monique; Möller, Harald E.
Abstract A procedure to prevent the formation of image and spectral Nyquist ghosts in echo‐planar spectroscopic imaging is introduced. It is based on a novel Cartesian center‐out echo‐planar spectroscopic imaging trajectory, referred to as EPSICO, and combined with a correction of the gradient‐echo phase and time shifts. Processing of homogenous sets of forward and reflected echoes is no longer necessary, resulting in an optimized spectral width. The proposed center‐out trajectory passively prevents the formation of Nyquist ghosts by privileging the acquisition of the center k‐space line with forward echoes at the beginning of an echo‐planar spectroscopic imaging dwell time and by ensuring that all k‐space lines and their respective complex conjugates are acquired at equal time intervals. With the proposed procedure, concentrations of N‐acetyl aspartate, creatine, choline, glutamate, and myo‐inositol were reliably determined in human white matter at 3 T. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.